A Bibliometric Analysis of Research on Knowledge Management in Tax Administration - Dewi, Annisa Puspita; Tjakratmadja, Jann Hidajat; Hendarman, Achmad Fajar (JDM (Jurnal Dinamika Manajemen), 2022)
Knowledge Management (KM) is crucial in the public sector, especially for tax administration. The aim of this study is to review the literature of KM in tax administration and outlining a future research agenda. This study uses bibliometric approach with data collected from the international academic database such as Proquest, Science Direct, Scopus, and Google Scholar. Finally, 83 articles from a variety of academic journals specializing in the field of Knowledge Management and Tax Administration used in this study. The result found that Iran and UK lead the world regarding the number of research publications in the area KM in tax administration. Considering the publication period, 2019 and 2020 are the most productive years regarding publication in this field. The analysis of the co-occurrence network of the literature resulted four clusters represent issue such as: (i) emerging information and communication technology (ICT) support KM implementation, (ii) critical success factor (CSF) and investigation the relation of KM process toward organization’s performance, (iii) knowledge management framework and its relation toward tax knowledge, and (iv) knowledge sharing in KM implementation. This study is the first study that explore KM literature within tax administration by using bibliometric